PERFORMANCE ANALYSIS OF LINEAR ARRAY ANTENNA IN RADAR SYSTEM THROUGH ANALYTICAL METHOD AND COMPUTATION METHOD VIA DFT - Hossam-E-Haider, Wg Cdr Dr Md.; Rahman, Afia Binte; Ali Khan, Maj Mohammed; Fardous Popy, Jannatul (R&D Wing, MIST, 2012)
It is important to design RADAR antennas with more energy radiated in some particular directions and less in other directions. Different types of antennas and their radiation patterns are evaluated. This is tantamount to requiring that the radiation pattern should be concentrated in the actual direction of interest. This is hardly achievable with a single RADAR antenna which has a specific radiation pattern. But with the use of the several antennas working together, it is possible to improve the radiation according to suit some specific requirements. In this study we have dealed with the most common linear array antenna. The equation of the electric field radiation pattern is derived with detail discussion on array tapering. Simulation result shows the radiation pattern in one direction with lowered side lobes, indicates the improvement of the wave propagation through the RADAR antenna.
Keywords: Array Factor (AF), Discrete Fourier Transform (DFT), Radiation Pattern, Main Beam, Side Lobe.